Dental Health of Bed-ridden Elderly at Home in Higashiyodogawa Ward, Osaka - Fujita, Masuhisa; Komemushi, Kazuko; Kihara, Hidefumi; Miyoshi, Kazuko; Yoshida, Yutaka; Fujimoto, Yoshiharu (Ronen Shika Igaku, 1996)
The City of Osaka conducted investigation, as a measure to monitor the dental health of bed-ridden elderly people cared at home, with questionnaire surveys (11/1/92 to 1/31/93) and a home visit program (1/12/93 to 3/31/93). The dental health status and needs of all bed-ridden elderly people 65 years of age or older residing in four wards of Osaka (east; Joto, west; Taisho, south; Higashisumiyoshi, and north; higashiyodogawa) were examined. This study has spawned a home dental care program using portable dental examination kits supplied by the Osaka City Environment and Health Agency, which has been in progress since June 1, 1994. The authors report in this paper the status of both this program and the home dental careconducted in the Higashiyodogawa Ward. The subjects of the survey were 52 people, 65 years or older, who were residing in the above four wards, had been designated as bed-ridden (grade B or C of the evaluation criteria of the Ministry of Health and Welfare), and had requested a home health care. Of these 52 subjects, 26 people (50%) requested dental examinations and 29 people (56%) were judged to require a professional dental care by dentists participating in the program. Eight patients were visited by participating dentists in the Higashiyodogawa Ward between June 1, 1994 and March 31, 1995, with the number of the total visits amounting to 55. This study indicates the need to improve the oral health of the bed-ridden elderly and to promote a dental health instruction and home dental care. The authors believe that additional upgrading of this program would benefit improvement of the oral health and welfare of the bed-ridden elderly people who are cared at home.